Study on Trading Pricing of Emission Rights of Enterprises - CHEN Jie; SHI Yixuan (Renmin Zhujiang)
The compensated use of emission rights is an effective means to control pollution. At present,there is no effective market pricing system for emission right trading.On the basis of analyzing the factors influencing the benchmark price of emission rights,the influencing factors were quantified,and a benchmark pricing index system of emission rights including eight first-level indexes and 26 second-level indexes was established.Based on the entropy weight method,the benchmark pricing model of emission rights was constructed,and the empirical analysis was carried out in 34 provinces (municipalities and autonomous regions),which provided a reference for the initial pricing of emission rights and the pricing of emission rights in the secondary trading market.